How to do everything with Google tools - Baker, Donna L. (McGraw-Hill, 2008)
How to Do Everything with Google Tools shows you that Google is so much more than a search engine, offering other features such as shopping, mapping, blogging, advertising, and much more. You'll also learn to use the email, communication, document, and spreadsheet tools that make up Google Apps. This book shows you how to maximize the Google tools that can make your work more efficient, your business more profitable, and your online experience more fun.